Analisis Penerapan Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam di Sekolah Alam Cikeas - Azwar Abdurakhman; Noor Albar; Fariz Fudla Fasih; Muhammad Hafiz; Ika Kartika (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to analyze the application of the Merdeka Curriculum in learning Islamic Religious Education at the Sekolah Alam Cikeas. This research uses a qualitative approach with data collection techniques in the form of literature reviews, observations, interviews and documentation. The research results show that the application of active learning methods with a holistic approach such as: Nature Based Learning, Experience Based Learning, Fun Learning and Project Based Learning can create an atmosphere interactive classes, encourage student participation, and foster a deeper understanding of teaching materials such as faith, worship, and morals. In this way, students' religious understanding can be significantly improved, so that they are able to practice Islamic teachings in their daily lives.